Blended Learning toward the Lifelong Learning Competence in Higher Education: An Overview from the Perspective of Students with Disabilities - Arini, Fitri Dwi; Rahmayanti, Elsa; Dalimunthe, Hanifa Laura (Journal of Education Reseach and Evaluation, 2025)
Lifelong learning (LLL) is essential for personal and professional growth. Despite its importance, research on LLL competencies is limited. This study explores the development of LLL competencies among college students with disabilities in a blended learning environment. This type of research uses a quantitative cross-sectional approach. The method used to collect data is a questionnaire. The data collection instrument uses a questionnaire sheet. This study involved 30 college students with disabilities. It used Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine four main factors influencing LLL competencies: access to information and literacy, openness to learning, self-direction, and self-evaluation. The results revealed that access to information, literacy, self-direction, and openness to learning did not significantly affect LLL competencies. However, curiosity emerged as a significant factor, highlighting its critical role in developing LLL skills. These findings suggest that fostering curiosity should be a priority in designing educational approaches for college students with disabilities. Higher education institutions can better prepare students for lifelong learning and professional success by nurturing this trait. This study underscores the importance of targeted strategies in blended learning environments to enhance the development of critical competencies among students with disabilities.